2013
DOI: 10.1002/pat.3120
|View full text |Cite
|
Sign up to set email alerts
|

Study on the thermal degradation behavior and flame‐retardant property of polylactide/PEDPP blends

Abstract: A phosphorus‐containing polyester, poly (ethylene diglycol phenylphosphinate) (PEDPP) was synthesized from phenylphosphonic dichloride and ethylene diglycol. The structure of PEDPP has been determined by Fourier transform infrared (FTIR) spectroscopy, 1H nuclear magnetic resonance and matrix assisted laser desorption ionization‐time of flight‐mass spectrometer. A series of polylactide (PLA) blends with various content of PEDPP as flame retardant was prepared by direct melt compounding; the PLA/PEDPP blend is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…On the other hand, the char payers can delay further combustion of the molten area. 29 Figure 7 (PU-10) shows that bubbles are uniformly distributed on the char layer, which may be because gas-phase FRs form volatile nitrogen elements (such as NO and NO 2 ) during the combustion process. For one thing, the volatilization of the nitrogen oxide absorbs lots of heat, and for another, nitrogen oxide reduces the concentration of oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the char payers can delay further combustion of the molten area. 29 Figure 7 (PU-10) shows that bubbles are uniformly distributed on the char layer, which may be because gas-phase FRs form volatile nitrogen elements (such as NO and NO 2 ) during the combustion process. For one thing, the volatilization of the nitrogen oxide absorbs lots of heat, and for another, nitrogen oxide reduces the concentration of oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the oxygen and heat were blocked by the char layers. On the other hand, the char payers can delay further combustion of the molten area Figure (PU-10) shows that bubbles are uniformly distributed on the char layer, which may be because gas-phase FRs form volatile nitrogen elements (such as NO and NO 2 ) during the combustion process.…”
Section: Resultsmentioning
confidence: 99%
“…The UL-94 flammability testing showed that it was an effective flame retardant for PLA and was able to self-extinguish flames in less than 2 s to achieve V-2 and V-0 ratings at polyphosphonate mass percentage of 5% and 15%, respectively. But it did not affect the materials' diglycol [13]. The limited oxygen index value (LOI) increased from 19.7% for pure PLA to 29.0% for the blend containing 10 wt% PEDPP.…”
Section: Introductionmentioning
confidence: 92%
“…The second step at between 380 o C and 430 o C in nitrogen and air is due to the pyrolysis of the main chain and formation of char residues. As for the third step under nitrogen, it may be attributed to further decomposition of the generated char residues to form the final char[13,24,25]. The amount of final char is about 45.3 wt% in nitrogen, while the value is about 22.0 wt% in air.…”
mentioning
confidence: 98%
“…The phosphorus‐containing flame retardants are often used as additives or incorporated into the PLA chain during its synthesis to modify the flammability of PLA and are active in the condensed and/or vapor phase . In the condensed phase, the thermal decomposition of the phosphorus‐containing flame retardants leads to the production of phosphoric acid, which condenses readily to produce pyrophosphoric acids and polymeric (PO 3 H) n .…”
Section: Introductionmentioning
confidence: 99%